2007
DOI: 10.1016/j.nima.2007.05.168
|View full text |Cite
|
Sign up to set email alerts
|

Operation of gas electron multipliers in pure xenon at low temperatures

Abstract: Operation of Gas Electron Multiplier (GEM) in ultra-pure xenon was studied for gas at 25 1C, cold but not saturated gas at À90 1C and saturated xenon vapour at À102 1C. The most stable operation was observed at À90 1C for which the maximum visible gain of 150 was obtained from a single GEM. The maximum gain of E40 was achieved for saturated xenon vapour at À102 1C and of E25 for twophase configuration at the same temperature. Continuous operation of a GEM in two-phase mode for periods of several hours was rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
4
6
0
Order By: Relevance
“…It was also observed that the liquid temperature had a significant effect on gain -higher gains could be achieved at lower temperature [304,299], which is consistent with the vapor density considerations. An increase from 165 K to 171 K (from P eq ≈ 1.87 bar to P eq ≈ 2.6 bar) resulted in the decrease of G max from 150 to about 25.…”
Section: Electron Multiplication With Micro-pattern Structuressupporting
confidence: 83%
See 1 more Smart Citation
“…It was also observed that the liquid temperature had a significant effect on gain -higher gains could be achieved at lower temperature [304,299], which is consistent with the vapor density considerations. An increase from 165 K to 171 K (from P eq ≈ 1.87 bar to P eq ≈ 2.6 bar) resulted in the decrease of G max from 150 to about 25.…”
Section: Electron Multiplication With Micro-pattern Structuressupporting
confidence: 83%
“…Gas condensation in the holes of avalanche devices has been reported as a likely reason for temporary failure of GEMs [304], LEMs [312] and RETGEMs [298], for double-phase argon as well as xenon. In some instances this could be reversed with thermal cycling.…”
Section: Electron Multiplication With Micro-pattern Structuresmentioning
confidence: 99%
“…Irrespective of the choice of charge readout device, the maximum charge gain drops with increasing gas pressure and therefore density [28] due to the decrease of the electron impact ionisation yield in the reduced electric field (E/P) within the avalanche region, and the limit due to breakdown imposed on the potential difference between the electrodes. This effect has also been noted in cryogenic gas due to the increased density as demonstrated within this report and also using cascaded GEMs [27,29] and resistive electrode thick gas electron multipliers (RETGEMs) [27].…”
Section: Discussionsupporting
confidence: 70%
“…At cryogenic temperatures, the maximum achievable gain in all gases is expected to drop due to the increase in gas density, as recently demonstrated with cascaded GEMs [10], [11] and in Resistive Electrode Thick GEMs (RETGEM) [21].…”
Section: Summary and Discussionmentioning
confidence: 87%
“…Some use avalanche multiplication in discrete holes, as to reduce to minimum possible secondary effects due to avalanche-induced photons; others use secondary scintillation, induced by electrons drifting in the gas phase, detected by photomultipliers [6]. In charge-multiplication mode, cascaded Gas Electron Multipliers (GEM), with holes approximately 50 microns in diameter, were shown to operate in noble gases at cryogenic temperatures, including in two-phase conditions [10], [11], [17]; their limited gain could have resulted from condensation of the very cold gas within the tiny holes. There have been other suggestions of using "optimized GEM" multipliers [18], "Large Electron Multipliers" (LEM) [19], -2 -MICROMEGAS [20] and more recently Resistive Thick GEMs (RETGEM) [21].…”
Section: Introductionmentioning
confidence: 99%